Entre sendas pós-coloniais e pós-modernas: análise intermidiática de O retrato do rei e Bacurau - Dellani, Lais dos Santos (2023)
This essay conducts an intermediatic analysis of the movie Bacurau (2019) by Juliano Dornelles and Kleber Mendonça Filho, and the book O Retrato do Rei (1991) by Ana Miranda. This research is based on the premise of the inexistence of post-modern and post-colonial intermidiatic debates amongst these works. It was made a literature review of the post-modern theories through authors such as Linda Hutcheon (1991) to delimit the borders of postmodernism, Claus Clüver (2006), to elucidate intermediality, and Hommi Bhabha (1998), to clarify the post-colonialism. Furthermore, an investigation of the author and directors was carried out in order to contextualize them in these theories, as well as their works. And, through this relation, it was proposed to establish a critical analysis of the works that have Brazil as their focus, as well as the social-historical construction and the misfortunes of the country. The results of the analysis indicate the post-modern and post-colonial elements are present explicitly and implicitly through the texts and intertextuality in the works.